2019
DOI: 10.1111/jcmm.14363
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting α7‐nAChR exerts cardioprotective effects on ischemic cardiomyopathy via activation of AMPK signalling

Abstract: Our previous studies have reported that agonist of α7 nicotinic acetylcholine receptors prevented electrophysiological dysfunction of rats with ischaemic cardiomyopathy (ICM) by eliciting the cholinergic anti‐inflammatory pathway (CAP). Adenosine monophosphate‐activated protein kinase (AMPK) signalling is widely recognized exerting cardioprotective effect in various cardiomyopathy. Here, we aimed to investigate whether the protective effects of the CAP are associated with AMPK signalling in ICM. In vivo, coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Their further study confirmed that repeated intrathecal injection of PHA-543613 during the perioperative period shortened the duration of post-surgical pain after SPS and suppressed SPS-potentiated microglia activation, which was also abolished by pretreatment with MLA (Sun et al, 2019). Consistently, Ji et al (2019) validated that intrathecal injection of PHA-543613 significantly alleviated spinal nerve ligation-induced neuropathic pain by decreasing dynorphin A concentration in the ipsilateral spinal cord. Furthermore, Umana et al (2017) revealed that both systemic and intra-vlPAG administration of PHA-543613 significantly attenuated formalin-induced inflammatory pain, which was completely abolished by pretreatment with MLA.…”
Section: Selective α Nachr Agonistsmentioning
confidence: 64%
“…Their further study confirmed that repeated intrathecal injection of PHA-543613 during the perioperative period shortened the duration of post-surgical pain after SPS and suppressed SPS-potentiated microglia activation, which was also abolished by pretreatment with MLA (Sun et al, 2019). Consistently, Ji et al (2019) validated that intrathecal injection of PHA-543613 significantly alleviated spinal nerve ligation-induced neuropathic pain by decreasing dynorphin A concentration in the ipsilateral spinal cord. Furthermore, Umana et al (2017) revealed that both systemic and intra-vlPAG administration of PHA-543613 significantly attenuated formalin-induced inflammatory pain, which was completely abolished by pretreatment with MLA.…”
Section: Selective α Nachr Agonistsmentioning
confidence: 64%
“…Thus, immunohistochemistry was performed to examine cardiac macrophage infiltration. In a prior study, stimulating the CAP was shown to promote the transformation of Ly-6C high macrophages to Ly-6C low macrophages in the late infarction phase [ 17 ]. Similarly, our results showed that cholinergic evocation reduced the accumulation of M1 macrophages and increased M2 macrophages infiltration in the peri-infarct area.…”
Section: Discussionmentioning
confidence: 99%
“…B7007, USA) was dissolved in 0.2% DMSO organic solvent and thoroughly oscillated at 37°C until the particles had completely dissociated. Cholinergic stimulation was conducted for 4 weeks with PNU-282987 (1 mg/kg) via a slow intraperitoneal injection for 2 minutes in the CHF rats [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is encoded by AHRNA7 on chromosome 15q14 and is widely expressed on the surfaces of inflammatory cells including macrophages, monocytes, T cells, B cells, and dendritic cells. [72] , [73] , [74] , [75] …”
Section: The Role Of the Cholinergic Anti-inflammatory Pathway (Cap) mentioning
confidence: 99%